Hydrogen-anion formation near a (2×1)-reconstructed Si(100) surface: Substrate-electronic-structure and trajectory dependence - Obreshkov, Boyan; Thumm, Uwe (My University, 2011)
We calculated the yield of outgoing hydrogen negative ions after the reflection of 1-keV neutral hydrogen atoms from a (2×1)-reconstructed Si(100) surface. We find that the charge-transfer dynamics at the reconstructed surface is dependent on both the surface-electronic structure and orientation of the projectile trajectory relative to the crystal azimuthal directions. Our results are in good quantitative agreement with the measured H− fractions of Maazouz and Esaulov [Surf. Sci. 398, 49 (1998)] for scattering trajectories that are aligned perpendicularly to rows of silicon dimers.